Aktivitas Matematika Berbasis Budaya pada Masyarakat Lampung - Rakhmawati, Rosida (Universitas Islam Raden Intan Lampung, INDONESIA, 2016)
Culture-based education has a vital role of individuals and communities to achieve progressivity in all aspects of life. Math-based culture called ethnomathematics is an approach that can be used to explain the role of mathematics in a multicultural society. Mathematical concepts used to explore the existence of mathematics in culture, especially traditional societies of Lampung. This study aims to describe the results of exploration Lampung Ethnomathematics with this kind of exploratory research as well as an ethnographic approach. The results showed that without studying the mathematical concept, traditional society of Lampung have applied these concepts in their daily lives using ethnomathematics. Proved the existence of mathematical concepts contained in custom home building, the local unit of Lampung, geometric shapes motif of tapis, as well as traditional games Lampung. Researchers suggest the results of this study to (a) used as alternative ideas mathematics learning outside the classroom, (b) introduced in learning formal mathematics as initial capital to teach the concept of mathematics to students, (c) be used as reference material for preparing a matter of mathematical problem-solving context.